Empowerment of the Disability Community through the Formation of Disability Cadres - Lisa, Harti Rahmi Aunurul; Arininta, Nungki; Ekawati, Fitriana Muriya (Faculty of Medicine, Public Health, and Nursing, 2024)
Background people with disabilities are a vulnerable group in society and often face various obstacles in accessing basic services. Physical barriers, lack of information and lack of comprehensive services are the main obstacles that hinder access to adequate health services. The implementation of Posbindu has not included people with disabilities so far so there is no health data from people with disabilities. This problem shows that there is a significant gap in health services for people with disabilities. Objective to fill the gap in health services for the disabled community. Method Parcipatory Action Research (PAR) with data collection by interview and Focus Group Discussion (FGD). The data was analyzed using a qualitative method using a thematic analysis approach. Results The six main factors faced by people with disabilities in accessing health services in the Kapanewon Kretek area are technical obstacles in accessing health services, limited physical access to health facilities, lack of proactive services, lack of program socialization, limited infrastructure and lack of family motivation. Intervention actions with a participatory approach involving people with disabilities as cadres in the implementation of disability-inclusive Posbindu. Discussion Community empowerment with a participatory community approach is an important step to overcome the gap in access to health services for people with disabilities in the Kapanewon Kretek area. The results of the evaluation of the implementation of cadre training showed a significant increase in cadre knowledge and skills, although practical implementation challenges remained. Recommendations for empowerment development are increasing the duration of training content, continuous assistance, the existence of special modules for cadres with disabilities, periodic evaluation and monitoring, increased family participation, cross-sector collaboration and the development of inclusive policies